Reflection Of Children’s Happiness By Coraline’s Character In Coraline Film - Sugiyono, Rafaela; Natsir, M; Lubis, Indah Sari (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This study concerns the reflection of a children's happiness in the Coraline film. The purpose of this study is to find some reflections of the happiness of Coraline's character through the situations described in the film that can be seen from several aspects. This study used the theory of happiness by Martin Seligman. Happiness has five aspects consisting of (1) Positive Emotion, (2) Engagement, (3) Positive Relationship, (4) Meaning and (5) Accomplishment. This research included qualitative descriptive research, this study used qualitative research to analyze the problems associated with happiness on the Coraline's character and in this study the approach applied a psychological approach, the data source was taken from the Coraline Film. The researcher used qualitative research to analyze the dialogue script of Caroline's character in the Coraline included in the aspects of happiness by Martin Seligman's theory. The results of the study showed that the happiness found in Caroline's character in the film is not all through the right way. When Coraline finds a home from another world, and there is a family that is very similar to her real family, Coraline begins to feel the happiness she gets when living conditions are fine. In fact, all of that is not a real happiness, but rather create problems for Coraline's life. Thus, from every feeling of happiness that Coraline’s feels, she tries to recognize and feel that not all the happiness she feels is real happiness according to what she wants to achieve.